2021
DOI: 10.15345/iojes.2021.04.012
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Social Emotional Learning Competencies and Life Satisfaction in Adolescents: Mediating Role of Academic Resilience

Abstract: Social-emotional learning (SEL) competencies has been the subject of many studies. The purpose of this study was to examine the mediating role of academic resilience in the relationship between adolescents' social-emotional learning competencies and life satisfaction. The study group was composed of 371 adolescents. Self-report measurement tools were used in the study. Structural equation modeling was used to investigate the mediating role of academic resilience in the relationship between social-emotional lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Indeed, social and emotional competencies has been demonstrated as a predictor of life satisfaction (Branquinho et al, 2023;García-Martínez et al, 2023;Turan, 2021). Branquinho et al (2023) revealed the significant influence of social and emotional competencies on the life satisfaction of young individuals.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…Indeed, social and emotional competencies has been demonstrated as a predictor of life satisfaction (Branquinho et al, 2023;García-Martínez et al, 2023;Turan, 2021). Branquinho et al (2023) revealed the significant influence of social and emotional competencies on the life satisfaction of young individuals.…”
mentioning
confidence: 97%
“…In this context, the management and regulation of emotions are considered crucial for maintaining adaptive psychosocial functionality during adolescence (Turan, 2021). Therefore, interventions based on Social and Emotional Learning are experiencing increased prominence and could be considered a protective factor to address the challenges arising from the pandemic (Turan, 2021).…”
mentioning
confidence: 99%
See 3 more Smart Citations